2008
DOI: 10.1542/peds.2007-2716
|View full text |Cite
|
Sign up to set email alerts
|

Common Metabolic Profile in Infants Indicating Impaired Cobalamin Status Responds to Cobalamin Supplementation

Abstract: Cobalamin supplementation changed all markers of impaired cobalamin status (low cobalamin, high total homocysteine, and high methylmalonic acid levels) toward a profile observed in cobalamin-replete older children and adults. Therefore, the high total homocysteine and methylmalonic acid levels reported for a large fraction of infants reflect not immature metabolism but rather insufficient cobalamin levels to fully sustain cobalamin-dependent reactions fully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 214 publications
(357 reference statements)
3
77
1
Order By: Relevance
“…The most repeated reason for risk of bias across the studies was an inadequate explanation about the drop-outs and an inadequate assessment of exposure (method to assess vitamin B 12 intakes). (31) ) or MMA (two studies (28,31) , while in one study (31) , associations were not found for MMA).…”
Section: Pregnant and Lactating Womenmentioning
confidence: 93%
See 2 more Smart Citations
“…The most repeated reason for risk of bias across the studies was an inadequate explanation about the drop-outs and an inadequate assessment of exposure (method to assess vitamin B 12 intakes). (31) ) or MMA (two studies (28,31) , while in one study (31) , associations were not found for MMA).…”
Section: Pregnant and Lactating Womenmentioning
confidence: 93%
“…In the RCT from Bjorke-Monsen et al (28) , the intervention was the strongest predictor of changes for all blood indices (regression coefficient 5 183 for serum vitamin B 12 In the Guatemalan cross-sectional study (30) , mean intake of vitamin B 12 was 3?1 mg/d for mothers and 2?2 mg/d for infants at the age of 12 months and the accompanying mean (SD) plasma vitamin B 12 concentration in mothers and infants was 114?4 (9?2) g/l and 262?2 (163?5) pmol/l, respectively. The plasma vitamin B 12 concentrations of the infants were correlated with maternal concentrations and they were also positively associated with infant B 12 intake from complementary foods (r 5 0?16, P , 0?0001).…”
Section: Infantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized study in Norway, intramuscular injection of 400 μg of vitamin B12 to infants (n = 54) at 6 weeks raised serum B12 (IQR: 291-497 pmol/L), and lowered MMA (from 0.58 to 0.20 μmol/L) and tHcy (from 7.46 to 4.57 μmol/L) at 4 months, compared to a group (n=51) that received no intervention [86]. Despite the high prevalence of vitamin B12 deficiency amongst pregnant and breastfeeding women and their infants, there is a paucity of information on infant development in response to vitamin B12 supplementation during pregnancy or infancy.…”
Section: Citationmentioning
confidence: 99%
“…Monsen et al [86] RCT in Norway. n=107 infants (6 wk) randomized to receive either an intramuscular injection of B12 (400 μg) or no intervention (control).…”
Section: Citationmentioning
confidence: 99%